2010
DOI: 10.1111/j.1365-2044.2010.06248.x
|View full text |Cite
|
Sign up to set email alerts
|

Litigation related to regional anaesthesia: an analysis of claims against the NHS in England 1995–2007*

Abstract: SummaryWe analysed 366 claims related to regional anaesthesia and analgesia from the 841 anaesthesia . Non-obstetric claims were more likely to relate to severe outcomes than obstetric ones. The maximum values of claims were higher for claims related to neuraxial blocks and eye blocks than for peripheral nerve blocks. Despite many limitations, including lack of clinical detail for each case, the dataset provides a useful overview of the extent, patterns and cost associated with the claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 27 publications
0
54
0
Order By: Relevance
“…In the case series by Kinsella et al, 3 (12%) out of the 25 parturients complained of intra-operative pain [12]. As intra-operative pain is the most common cause of litigation in obstetric anaesthesia, appropriate selection and discussion with patients are essential if one decides to accept a lower block height in an emergency scenario [16], and it is especially important to warn the woman that she may experience some discomfort until the baby is born. Taking 4-8 full vital capacity breaths, rather than traditional three-minute pre-oxygenation before induction of general anaesthesia, is an acceptable option [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the case series by Kinsella et al, 3 (12%) out of the 25 parturients complained of intra-operative pain [12]. As intra-operative pain is the most common cause of litigation in obstetric anaesthesia, appropriate selection and discussion with patients are essential if one decides to accept a lower block height in an emergency scenario [16], and it is especially important to warn the woman that she may experience some discomfort until the baby is born. Taking 4-8 full vital capacity breaths, rather than traditional three-minute pre-oxygenation before induction of general anaesthesia, is an acceptable option [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the other paper referenced to support this claim in fact found no significant difference in the incidence of failed intubation over their 6-year study period [3]. A more recent audit by Saravanakumar and Cooper [4], looking at 1988-2004, showed an increase in failed intubation rate that again did not reach statistical significance. If a trend does exist, there are other factors to consider in addition to lack of practice.…”
mentioning
confidence: 94%
“…We have recently published several papers describing anaesthesia related claims against the National Health Service Litigation Authority (NHSLA) [1][2][3][4]. This letter serves to report, in brief, aspects of claims relating to obstetric general anaesthesia not reported in those papers and provides some comparison with obstetric regional anaesthesia claims [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing accountability of the medical profession and an increased emphasis on patient safety [13]. A recent review of claims handled by the National Health Service Litigation Authority (NHSLA) between 1995-2007 revealed that 366 of 841 cases (44%) were related to regional anaesthesia and of these, half arose in the obstetric setting [14]. Examples of claims included neurological damage following labour epidurals, dural puncture leading to headache and backache, and pain during labour and caesarean section.…”
Section: Introductionmentioning
confidence: 99%